Analisis Pelunakan Air (Water Softening) Dengan Metode Demineralisasi Di PT. DMC Teknologi Indonesia Jababeka 2 Cikarang - Akbar Gifari; Siti Aliyah; Samsul Ma'arif; Dodit Ardiatma (DPPM Universitas Pelita Bangsa, 2022)
The water softening process is a process that functions as a decrease in the concentration of calcium, magnesium, and other ions in the hard water category. This process reduces or eliminates water hardness so that water with low mineral content is obtained. Softening itself is used as a pre-treatment method to reduce hard water before entering the reverse osmosis process. Demineralization is a process of removing mineral salts in water such as calcium (Ca) and magnesium (Mg), so that the water produced has a high purity. The purpose of this research is to find out an overview and what materials are used in the water softening process, to know the character of the ion exchange resin on the machine, to know the results of measuring water after going through the softening process by comparing it with the quality standards that have been set at PT. DMC Teknologi Indonesia. The research method used is descriptive. Based on the results of the direct measurement in the field using a manual measuring instrument, it shows the value of the conductivity parameter, and TDS is still below the standard set by the company. The pH value of demin water tends to be close to acid, in the demineralization process to get light water. with a low conductivity value and a TDS value that is close to 0, PT DMC Teknologi Indonesia uses 2 times the reverse osmosis (RO) process, namely at the beginning and at the end. The demineralization process at PT DMC Teknologi Indonesia uses cation resin with HCl regenerant and anion resin with NaOH regenerant. Keywords: Water Softening, Demineralization, Conductivity, TDS, pH